China’s Religious Promotion Along the Trans-Himalaya Region - Langeh, Abhigya (International Journal of Advanced Research in Peace, Harmony and Education, 2024)
Religion has shaped many nations’ politics, including China’s. Religion is strictly regulated and controlled by the government because of the country’s communist philosophy. Traditional Chinese religion includes Confucianism, Taoism, Buddhism, and folk religion. Confucianism promotes order and hierarchy, which has affected the Chinese border administration. Border security officers and border crossing laws and regulations are selected and trained using Confucian ideas. Taoism emphasises harmony and balance, which has influenced Chinese border management. Taoist ideas have shaped border crossings and how officials treat passengers, emphasising peace and respect. Indian Buddhism also influenced the Chinese border administration. China’s border security reflects Buddhist precepts of compassion and nonviolence. Chinese border officers are trained to be polite yet tough when managing borders. That being said, the Chinese government has implemented policies and practices related to religion in border regions, particularly in Tibet and Xinjiang. In these areas, the government has been accused of suppressing the religious practices of minority groups, including Tibetan Buddhists and Uighur Muslims, under the guise of national security and border control. This has resulted in a significant amount of controversy and criticism from human rights organizations and international observers. While Chinese religion may play a role in certain aspects of society and culture, it is not typically a direct factor in border management. However, the Chinese government’s policies related to religion in border regions have been very much present in the region. This research uses a qualitative method to evaluate Chinese religion’s impact on border control. It examines Chinese influence in Ladakh and Arunachal Pradesh in India and Nepal and Bhutan. Additionally, the article uses primary and secondary data. Primary data comprises government papers, treaties, and pronouncements from governing regimes, whereas secondary data includes articles, commentaries, and news.